Alteration of Pharmacokinetics of Grepafloxacin in Type 2 Diabetic Rats - Meguho Watanabe; Masaki Kobayashi; Jiro Ogura; Natsuko Takahashi; Hiroaki Yamaguchi; Ken Iseki (Frontiers Media S.A., 2014)
Purpose. Patients with type 2 diabetes are generally treated with various pharmacological compounds and are exposed to a high risk of drug-drug interactions. However, alterations of pharmacokinetics in a type 2 diabetes model have been obscure. The present study was undertaken to investigate the effects of type 2 diabetes on the pharmacokinetics of the fluoroquinolone grepafloxacin (GPFX) and the expression level of P-glycoprotein (P-gp), one of the drug efflux transporters. Methods. We used Goto-Kakizaki (GK) rats, a lean model of type 2 diabetes. Plasma concentration and intestinal, renal, and biliary clearance of GPFX were measured after intravenous and intraintestinal administration in Wistar and GK rats. Real-time PCR and Western blotting were used to assess mRNA and protein expression levels. Results. We found a significant increase in the plasma concentrations of GPFX at 90, 120 and 240 minutes after intraintestinal administration in GK rats compared with the concentrations in Wistar rats but not after intravenous administration. The increase in plasma GPFX concentration was associated with reduction in jejunal clearance of GPFX caused by a decrease in secretory transport of GPFX. However, there was no correlation between the decrease in secretory transport of GPFX and P-gp expression level. Conclusion. Type 2 diabetic conditions alter P-gp function as well as expression level and correlate poorly with each other.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.